Die verbogene Verfassung – zur Neuregelung der Bund-Länder-Finanzbeziehungen ab 2020 - Wolfgang Renzsch (Wirtschaftsdienst, 2017)
Anfang Juni 2017 haben der Deutsche Bundestag und der Bundesrat das Gesetz zur Neuregelung des bundesstaatlichen Finanzausgleichssystems beschlossen. Mit diesem Gesetz haben die Bundesländer wichtige Bestandteile ihrer föderalen Selbstbestimmung aufgegeben und den solidarischen Finanzausgleich aufgekündigt. Darüber hinaus weist das Gesetz erhebliche handwerkliche Mängel auf – insbesondere bezogen auf die Verfassungskonformität. – – The federal legislature has adopted a new system of intergovernmental fiscal relations from 2020 onwards which will change the federal structure of Germany considerably. In particular, the abolition of the horizontal equalisation among the Länder (Länderfinanzausgleich) and its replacement by an equalisation of fiscal power (Finanzkraftausgleich) within the distribution of the revenues of sales taxes changes the underlying structure of the German federal state fundamentally. The new legislation indicates this shift of the federal balance: the federation will take over the construction of motorways completely. Federal authorities also gain new powers in controlling the use of federal funds by the Länder. Instead of a balance of the federation and the Länder we will get a dominance of the federation.
Keywords: E61; E62; H77; 330